1984
DOI: 10.1103/physrevlett.52.2209
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Interpretation of the Secondary-Reaction Experiments in W Targets and Prospects for Production of Superheavy Elements in Ordinary Heavy-Ion Reactions

Abstract: A consistent interpretation is presented of spontaneous fission events previously observed in Hg sources separated from CERN W targets. The energy spectra are interpreted in terms of fission to four fragments with ZiXtotal) -320 MeV. The value of v is estimated to be between 3 and 5. The measured masses of the fissioning nuclei are consistent with various molecules of element 112 with about 160 neutrons. The prospects of producing superheavy elements with use of targets around W and projectiles like Sr and Zr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…In addition to their very long lifetimes, much longer than that of their corresponding normaldeformed ground states, they may decay by very enhanced α-particle emission, in II min to II min9 or III min to III min (the present work) transitions, or by very retarded α-particle decay, in II min to I min or in III min to II min transitions, 11 and also by longlived proton radioactivity. 10 It was shown that the existence of the isomeric states in the second and third well of the potential-energy surfaces enables one to understand, in a fully consistent manner, the production of the long-lived superheavy element with Z = 112, [3][4][5]37 much longer than seen in Ref. 39.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to their very long lifetimes, much longer than that of their corresponding normaldeformed ground states, they may decay by very enhanced α-particle emission, in II min to II min9 or III min to III min (the present work) transitions, or by very retarded α-particle decay, in II min to I min or in III min to II min transitions, 11 and also by longlived proton radioactivity. 10 It was shown that the existence of the isomeric states in the second and third well of the potential-energy surfaces enables one to understand, in a fully consistent manner, the production of the long-lived superheavy element with Z = 112, [3][4][5]37 much longer than seen in Ref. 39.…”
Section: Discussionmentioning
confidence: 92%
“…The experimental evidence for the existence of this element was based mainly on the observation of fission fragments in Hg sources which were separated from the CERN W target, 3 and on the mass measurements of the fissioning nuclei, which were interpreted as due to five different molecules of the isotope with Z = 112 and N ∼ = 160. 5 While it was impossible to disprove the data it seemed very difficult to understand them, 38 in particular the long lifetime of the observed activities of several weeks, and the large deduced heavy ion reaction cross section of a few mb. It was pointed out 5 that the radiative capture processes like 184 W( 88 Sr,γ) 272 112 or 186 W( 86 Sr,γ) 272 112 are possible at bombarding energies around the Coulomb barrier.…”
Section: Production Cross Sections Of the Various Isotopesmentioning
confidence: 99%
“…The existence of such long-lived isomeric states, with lifetimes much longer than those of their corresponding ground states, and with preferential production cross sections at relatively low bombarding energies, may add new considerations regarding the stability and the production mechanism of heavy and superheavy elements [3,[28][29][30]. In particular it should be mentioned that the extra-push energies needed for the production of such nuclei in their superdeformed and hyperdeformed wells are much smaller than expected for producing them in their normal states [31].…”
Section: Discussionmentioning
confidence: 99%
“…I and II were performed with a 125 MeV 28 Si beam and irradiation III with 135 MeV. Carbon catcher foils of 200 µg/cm 2 and 60 µg/cm 2 were used in order to catch the evaporation residue nuclei and their daughters.…”
Section: Introductionmentioning
confidence: 99%
“…Marinov et al [1] [2] [3] suggest that neutron deficient long lived isotopes of element 112 can exist and may be produced with higher cross-sections.…”
Section: Target Irradiation Periodmentioning
confidence: 99%